2020
DOI: 10.1007/s00701-020-04248-2
|View full text |Cite
|
Sign up to set email alerts
|

The dentato-rubro-thalamic tract as the potential common deep brain stimulation target for tremor of various origin: an observational case series

Abstract: Introduction Deep brain stimulation alleviates tremor of various origins. The dentato-rubro-thalamic tract (DRT) has been suspected as a common tremor-reducing structure. Statistical evidence has not been obtained. We here report the results of an uncontrolled case series of patients with refractory tremor who underwent deep brain stimulation under tractographic assistance. Methods A total of 36 patients were enrolled (essential tremor (17), Parkinson's tremor (8), multiple sclerosis (7), dystonic head tremor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
96
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(106 citation statements)
references
References 63 publications
5
96
0
Order By: Relevance
“…Accordingly, the limitation of not being able to accurately delineate the white matter tracts in dense areas of crossing, kissing, or branching fibers was prevented. In accordance with groups that used P-FT [1,9,35], we were able to show the tract's decussation instead of ipsilateral tracts resulted from D-FT [10][11][12][13][14][15]19]. In fact, studies comparing P-FT and D-FT showed higher anatomical precision using P-FT not only with tracking the DRT but also other white matter fibers such as the corticospinal tract and fornix [8,18,38].…”
Section: Mri Sequences Preprocessing and Fiber Trackingsupporting
confidence: 86%
See 1 more Smart Citation
“…Accordingly, the limitation of not being able to accurately delineate the white matter tracts in dense areas of crossing, kissing, or branching fibers was prevented. In accordance with groups that used P-FT [1,9,35], we were able to show the tract's decussation instead of ipsilateral tracts resulted from D-FT [10][11][12][13][14][15]19]. In fact, studies comparing P-FT and D-FT showed higher anatomical precision using P-FT not only with tracking the DRT but also other white matter fibers such as the corticospinal tract and fornix [8,18,38].…”
Section: Mri Sequences Preprocessing and Fiber Trackingsupporting
confidence: 86%
“…Two studies investigated systematically the antitremor effect of DRT neuromodulation on Parkinsonian tremor to date. Endpoints of these case series studies were tremor reduction either during 14 days postoperatively or immediately intraoperatively [14,35]. At this early time point, however, tremor improvement resulting from micro-lesional effects cannot be excluded.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, several clinical studies suggested a correlation between upper limb dystonia symptoms and MS tremor, supporting the idea of the involvement of cerebello-pallido-thalamo-cortical network dysfunction in the pathophysiology of MS tremor [ 23 ]. Moreover, neuroimaging (tractography) data obtained from patients who underwent deep brain stimulation (DBS) for tremor, including those with MS, highlighted the dentato-rubro-thalamic tract as the common stimulation target for DBS [ 24 ]. Recently, structural and functional magnetic resonance imaging studies revealed the involvement of cerebello-thalamo-cortical pathways in the generation of MS tremor [ 25 , 26 ].…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…The DRTT, which originates from the dentate nucleus in the cerebellum and terminates in the contralateral ventrolateral (VL) nucleus of the thalamus, is involved in movement control [2]. Therefore, abnormal movement such as ataxia can occur when the DRTT is injured [3][4][5][6][7][8][9][10][11][12]. In this case study, this patient showed severe dysmetria in his right hand and moderate ataxic gait.…”
Section: Lettermentioning
confidence: 75%